2012
DOI: 10.1126/scitranslmed.3003551
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Triggers Chronic Cardiac Autoimmunity in Type 1 Diabetes

Abstract: Patients with type 1 diabetes (T1D) suffer excessive morbidity and mortality following myocardial infarction (MI) that is not fully explained by the metabolic effects of diabetes. Acute MI is known to trigger a profound innate inflammatory response with influx of mononuclear cells and production of proinflammatory cytokines that are crucial for cardiac repair. We hypothesized that these same pathways might exert ‘adjuvant effects’ and induce pathological responses in autoimmune-prone T1D hosts. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 50 publications
3
61
0
5
Order By: Relevance
“…T ese mice were perhaps a disappointment in that they did not spontaneously develop T1D, but surprisingly, humanized DQ8 NOD mice did develop fatal myocarditis. T us begins a tale of bench to bedside that now culminates with the current report by Gottumukkala et al (1).…”
Section: Focusmentioning
confidence: 86%
See 1 more Smart Citation
“…T ese mice were perhaps a disappointment in that they did not spontaneously develop T1D, but surprisingly, humanized DQ8 NOD mice did develop fatal myocarditis. T us begins a tale of bench to bedside that now culminates with the current report by Gottumukkala et al (1).…”
Section: Focusmentioning
confidence: 86%
“…In a series of translational experiments, Gottumukkala et al (1) then showed that post-MI patients with T1D, but not T2D, expressed multiple autoantibodies directed against cardiac proteins (Fig. 1).…”
Section: Focusmentioning
confidence: 99%
“…Patients with type 1 diabetes have less favourable outcomes than non-diabetic patients after an acute coronary event, 110 a finding that might be explained by a recent report that, after myocardial infarction, patients with type 1 diabetes express antibodies to cardiac proteins, whereas patients with type 2 diabetes do not. 111 The risk for microvascular complications, including retinopathy, nephropathy, and neuropathy, decreases with intensive insulin therapy. Over the past 5 years, several large clinical trials have advanced the prediction and prevention of microvascular complications (table 1).…”
Section: Burden Of Type 1 Diabetes: Complications Excess Mortality mentioning
confidence: 99%
“…First, very low expression levels of particular self antigens in human mTECs correlate with a high frequency of cognate, auto-reactive T cells and/or autoantibodies in the case of the myosin heavy chain 6 93, 94 , an autoantigen in autoimmune myocarditis, or GAD65 95 and ZnT8, both targets in type 1 diabetes (B.K., S. Pinto, R. Mallone, unpublished observations). Genetic polymorphisms in regulatory regions of some autoantigens, which exert subtle effects on the expression level of self antigens in mTECs but not peripheral tissues correlate with susceptibility to organ-specific auto-immunity as shown for insulin and type 1 diabetes 96-98 , the alpha-chain of the acetylcholine receptor and myasthenia gravis 99 and the thyroid stimulating hormone receptor and Graves’ disease 100 .…”
Section: Perspectivesmentioning
confidence: 99%